2007
DOI: 10.1152/japplphysiol.00081.2007
|View full text |Cite
|
Sign up to set email alerts
|

CM-MM and ACE genotypes and physiological prediction of the creatine kinase response to exercise

Abstract: Exertional rhabdomyolysis (ERB) is a syndrome of severe skeletal muscle breakdown. Blood levels of creatine kinase (CK) are widely used as a marker to reflect muscle breakdown. Some individuals exhibit extreme increases in blood CK after exercise and have been characterized as high responders (HR), but no clinical definition of HR exists and reasons for the HR phenomenon are not understood. This study investigated possible associations between the magnitude of the CK response to exercise and polymorphisms of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
83
6
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(98 citation statements)
references
References 37 publications
6
83
6
3
Order By: Relevance
“…It has been reported that CK-MM polymorphism influence physiological responses to exercise [42,56]. Although our results did not demonstrate this association with the analyzed parameters, at least for the CK-MM TaqI polymorphism, the correlation found between this polymorphism and distance covered could compromise any possible association.…”
Section: Discussioncontrasting
confidence: 90%
“…It has been reported that CK-MM polymorphism influence physiological responses to exercise [42,56]. Although our results did not demonstrate this association with the analyzed parameters, at least for the CK-MM TaqI polymorphism, the correlation found between this polymorphism and distance covered could compromise any possible association.…”
Section: Discussioncontrasting
confidence: 90%
“…The CKMM AA genotype was associated with high values of VO 2 max and this result showed that Iranian athletes and non-athletes had more endurance potential (4). As the G allele is the rare allele for the CKM-NcoI polymorphism, researchers have speculated that this allele is associated with a protective mechanism against muscle breakdown (15).…”
Section: Discussionmentioning
confidence: 89%
“…It is believed that the A/G polymorphism is also associated with different CK-MM activities in myocytes (13). The frequency of the minor G allele in this type of polymorphism varies in the range from 15% in the Chinese population to 29% -35% in Caucasians and 32% in white Americans (14)(15)(16). Recently interdependence between the CK-MM A/G polymorphism and individual differences in the expression of the physical qualities of a person has been shown in several studies (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…However, the CK response to exercise shows great individual variability 9,26,27 because it is influenced by personal factors, such as gender, race, muscle mass, training status 23 , and genetic predisposition 28 . Therefore, the same training stimulus can cause different individuals to be classified as having a high or low response to increased [CK serum ].…”
Section: Comparison Of Different Ways Of Expressing Creatine Kinase Cmentioning
confidence: 99%